Model insights into energetic photoelectrons measured at Mars by MAVEN. Issue 21 (5th November 2015) - Sakai, Shotaro; Rahmati, Ali; Mitchell, David L.; Cravens, Thomas E.; Bougher, Stephen W.; Mazelle, Christian; Peterson, W. K.; Eparvier, Francis G.; Fontenla, Juan M.; Jakosky, Bruce M.
Abstract: Photoelectrons are important for heating, ionization, and airglow production in planetary atmospheres. Measured electron fluxes provide insight into the sources and sinks of energy in the Martian upper atmosphere. The Solar Wind Electron Analyzer instrument on board the MAVEN (Mars Atmosphere and Volatile EvolutioN) spacecraft measured photoelectrons including Auger electrons with 500 eV energies. A two‐stream electron transport code was used to interpret the observations, including Auger electrons associated with K shell ionization of carbon, oxygen, and nitrogen. It explains the processes that control the photoelectron spectrum, such as the solar irradiance at different wavelengths, external electron fluxes from the Martian magnetosheath or tail, and the structure of the upper atmosphere (e.g., the thermal electron density). Our understanding of the complex processes related to the conversion of solar irradiances to thermal energy in the Martian ionosphere will be advanced by model comparisons with measurements of suprathermal electrons by MAVEN. Key Points: Photoelectrons are diagnostic of solar energy deposited in atmosphere of Mars Low‐energy photoelectron fluxes depend on the ionospheric electron density Precipitation of external electrons contributes to measured electron fluxes